Heart Failure: Past, Present, Future - Karki, D. B.; Bhattarai, T. R.; Rayamajhi, A. (Kathmandu University Medical Journal, 2021)
There are 23 million people with heart failure in the world. Heart failure with reduced ejection fraction (HFrEF) and heart failure with preserved ejection fraction (HFpEF) need to be identified before advising treatment of heart failure. Coronary artery disease, dilated cardiomyopathy, valvular heart disease, and hypertension are the common causes of heart failure. Diuretics, angiotensin converting enzyme inhibitors, angiotensin receptor blockers, and neprilysin receptor blockers have been found to reduce mortality in heart failure. Natural compensatory mechanisms such as release of various vasoconstrictors and vasodilators in heart failure come into action to improve symptoms for some time. Ultimately compensatory mechanisms fail to work and patients reach end-stage heart failure. Mechanical circulatory support devices are recommended as a bridge treatment before heart transplant. The only option at this stage is heart transplant which is not feasible easily in the low and middle-income countries. Though end-stage heart failure treatment with inotropic drugs improves symptoms for a short period, various trials have shown increased mortality with their uses. On-going research on heart failure is expected to come out with more effective treatment of heart failure in future.